Effect of Different Dietary Levels of Energy and Sulfur-Containing Amino Acids, Lysine, and Threonine Levels on Productive and Economic Performance and Carcass Characteristics of Broiler Chickens - Golzadeh, Mohammad; Shahriar Maghsoudlou,; Gharhebash, Ashour mohammad; Bayat Koohsar, Javad (Journal of Poultry Sciences and Avian Diseases, 2025)
An experiment was conducted to investigate the effect of different energy levels and the concentration of methionine, lysine and threonine amino acids on production and economic performance of broiler chickens with the number of 180 Arbor-acres strain broiler chickens in a 3×2 factorial arrangement (2 levels of metabolizable energy, high: 2950, 3000 and 3050 and low: 2850, 2900 and 2950 for starter, grower and finisher phases, respectively × 3 different levels of amino acids methionine, lysine and threonine: the recommended level for Arbor-acres, 15% more and 15% less than that) and three repetitions in a completely random design. The results showed that using a higher level of dietary energy caused a significant increase in feed intake and weight gain in the entire growth period (p0.05), body weight was significantly affected by the concentration of amino acids in the diet (p0.05). Higher energy levels and higher concentrations of amino acids in the feed caused a significant increase in feed cost (p